Obesity and cardiovascular disease: An executive document on pathophysiological and clinical links promoted by the Italian Society of Cardiovascular Prevention (SIPREC) - Volpe, Massimo; Gallo, Giovanna (Frontiers in Cardiovascular Medicine, 2023)
The prevalence of obesity worldwide has increased in recent decades not only among adults, but also in children and adolescents. This phenomenon contributes to an increased risk of cardiovascular diseases (CVD), also after the adjustment for conventional risk factors such as hypertension, diabetes and dyslipidemia. Indeed, obesity contributes to the development of insulin resistance, endothelial dysfunction, sympathetic nervous system activation, increased vascular resistance and inflammatory and prothrombotic state which promote the incidence of major cardiovascular events. On the basis of this evidence, in 2021 obesity has been acknowledged as a definite pathological identity and identified as a recurrent, chronic non-communicable disease. Therapeutic strategies for the pharmacological treatment of obesity include the combination of naltrexone and bupropione and the lipase inhibitor orlistat and they have been recently implemented with the glucagon like peptide-1 receptor agonists semaglutide and liraglutide, which have produced positive and sustained effects on body weight reduction. If drug interventions are not effective, bariatric surgery may be considered, representing an efficacious treatment option for extreme obesity or obesity with comorbidities. The present executive paper is aimed to increase knowledge on the relationships between obesity and CVD, to raise the perception of this condition which is currently insufficient and to support the clinical practice management.